1997
DOI: 10.2169/internalmedicine.36.804
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's Syndrome due to Bilateral Adrenocortical Adenomas with Different Pathological Features.

Abstract: A 48-year-old womanwith Cushing's syndrome due to bilateral adrenocortical adenomas is reported. The patient presented with a typical Cushingoid appearance. The serum cortisol level was elevated with loss of the diurnal rhythm and the plasma adrenocorticotropic hormone (ACTH) level was undetectable. Dynamic testing showed no suppression of urinary 17-OHCSby high-dose dexamethasone and no stimulation by metyrapone. An abdominal computed tomography (CT) scan showed bilateral adrenal tumors. Bilateral adrenalecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Some studies have revealed that steroidogenic enzymes, such as P450scc, 3β-HSD, P450c21, P450c17, and P450c11, are intensely expressed in the compact cells of the adenoma, while their expression profiles are negative in the adjacent non-neoplastic cortex. At the same time, the histological features may differ between two adenomas[14,15]. It is difficult to distinguish between functioning or nonfunctioning adrenal cortical masses by the imaging characteristics on CT scanning[1].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have revealed that steroidogenic enzymes, such as P450scc, 3β-HSD, P450c21, P450c17, and P450c11, are intensely expressed in the compact cells of the adenoma, while their expression profiles are negative in the adjacent non-neoplastic cortex. At the same time, the histological features may differ between two adenomas[14,15]. It is difficult to distinguish between functioning or nonfunctioning adrenal cortical masses by the imaging characteristics on CT scanning[1].…”
Section: Discussionmentioning
confidence: 99%
“…The imaging method employing [6β‐ 131 I]iodomethyl‐19‐norcholesterol (NP‐59) was introduced in the late 1970s [23] as a means of assessing adrenal cortical function. The NP‐59 scan, performed with dexamethasone suppression, had the advantage of correlating autonomous cortical function (typically primary aldosteronism) with anatomical abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the diagnosis and management of corticotropin (ACTH)-independent Cushing syndrome (CS) or subclinical CS in patients with a unilateral cortical adenoma is relatively straightforward [1,2], the management of patients with bilateral adrenal masses in these settings is problematic [3][4][5][6][7][8][9][10][11][12]. These patients may have a unilateral cortisol-secreting adenoma with a contralateral nonfunctioning cortical adenoma, bilateral cortisol-secreting adenomas, or bilateral ACTH-independent macronodular adrenal hyperplasia (AIMAH) masquerading as bilateral single adenomas.…”
mentioning
confidence: 99%